Indonesian Cinnamon Competitiveness and Competitor Countries in International Market - Sa'diyah, Puteri Fadjria Insan; Darwanto, Dwidjono Hadi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2020)
Indonesia is the largest cinnamon producing country in the international market. The presence of competing countries causes competition for completed cinnamon demand in the international market. International trade requires that each country has specialization and the ability to be able to compete for existing markets. This study analyzes the competitiveness of Indonesia's cinnamon exports and the competitors (China, Vietnam, Sri Lanka, and Madagascar) by looking at comparative and competitive advantages along with factors that can influence them. The analysis period used in this study is from 2000 to 2017. Competitiveness analysis is measured byÂ  using the Trade Specialization Index (TSI) and Export Competitive Index (XCI) analysis methods, while the analysis of factors that can affect competitiveness performance is analyzed using the panel data regression method. The results of this study indicated that Indonesia and the competitors have comparative advantages and tend to be cinnamon exporting countries in the International Market, besides that Indonesia and competitors (China, Vietnam, and Madagascar) have competitive advantages and cinnamon exports of these countries increase from the previous year, so that the country was able to compete for cinnamon exports on the International Market. Factors that can affect the performance of the export competitiveness of cinnamon in Indonesia and competitors are productivity, market share, export prices, and domestic consumption.